2023
DOI: 10.1021/acsmedchemlett.2c00472
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Optimization of a Novel Macrocyclic Amidinourea Series Active as Acidic Mammalian Chitinase Inhibitors

Abstract: Our research group has been involved for a long time in the development of macrocyclic amidinoureas (MCAs) as antifungal agents. The mechanistic investigation drove us to perform an in silico target fishing study, which allowed the identification of chitinases as one of their putative targets, with 1a showing a submicromolar inhibition of Trichoderma viride chitinase. In this work, we investigated the possibility to further inhibit the corresponding human enzymes, acidic mammalian chitinase (AMCase) and chitot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Sugawara et al linked the 14-membered lactone of erythromycin to the N -methylcarbamoylguanidinyl to obtain a chitinase inhibitor EN30 with better activity than that of argifin (IC 50 value of 64 nM against Sm ChiB) . Dreassi et al identified the chitinase inhibitor AMC with submicromolar inhibitory activity ( K i value of 1.9 μM against AMCase) on mammalian acidic chitinase (AMCase) . All of these results demonstrated that the N -methylcarbamoylguanidinyl was a crucial active fragment of chitinase inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Sugawara et al linked the 14-membered lactone of erythromycin to the N -methylcarbamoylguanidinyl to obtain a chitinase inhibitor EN30 with better activity than that of argifin (IC 50 value of 64 nM against Sm ChiB) . Dreassi et al identified the chitinase inhibitor AMC with submicromolar inhibitory activity ( K i value of 1.9 μM against AMCase) on mammalian acidic chitinase (AMCase) . All of these results demonstrated that the N -methylcarbamoylguanidinyl was a crucial active fragment of chitinase inhibitors.…”
Section: Introductionmentioning
confidence: 99%